Procedure-Related Differences and Clinical Outcomes in Patients Treated with Percutaneous Coronary Intervention Assisted by Optical Coherence Tomography between New and Earlier Generation Software (Ultreon™ 1.0 Software vs. AptiVue™ Software) - Rafał Januszek; Wojciech Siłka; Karol Sabatowski; Krzysztof Piotr Malinowski; Grzegorz Heba; Sławomir Surowiec; Michał Chyrchel; Łukasz Rzeszutko; Leszek Bryniarski; Andrzej Surdacki; Krzysztof Bartuś; Stanisław Bartuś (Journal of Cardiovascular Development and Disease, 2022)
(1) Introduction: Optical coherence tomography (OCT) intravascular imaging facilitates percutaneous coronary intervention (PCI). Software for OCT is being constantly improved, including the latest version Ultreon™ 1.0 Software (U) (Abbott Vascular, Santa Clara, CA, USA). In the current analysis, we aim to compare processing results, procedural indices as well as clinical outcomes in patients treated via PCI. This was conducted using earlier generation OCT imaging software versions (non-U) and the newest available one on the market (U). (2) Methods: The study comprised 95 subsequent and not selected patients (55 processed with U and 40 non-U). The non-U processings were transferred for evaluation by U software, while the comparison of OCT parameters, selected clinical and procedural indices was performed between groups. We further assessed clinical outcomes during the follow-up period, i.e., major adverse cardiovascular events (MACE) and predictors of stent expansion. (3) Results: We did not detect any differences in general features between either of the assessed groups at baseline. Non-U software was more often used for bare-metal stenting (p = 0.004), while PCIs in the U group demanded a greater number of stents (p = 0.03). The distal reference of external elastic lamina (EEL) diameter was greater in the non-U group (p = 0.02) with no concurrent differences in minimal (p = 0.27) and maximal (p = 0.31) stent diameter. It was also observed that MACE was more frequently observed in the non-U group (p = 0.01). Neither univariable (estimate: 0.407, 95%CI: (−3.182) − 3.998, p = 0.82) nor multivariable (estimate: 2.29, 95%CI: (−4.207) − 8.788, p = 0.5) analyses demonstrated a relationship between the type of software and stent expansion. (4) Conclusions: Improvement in the software for image acquisition and processing of OCT is not related to stent expansion. The EEL diameter is preferably used to select the distal stent diameter in newer software.